2021
DOI: 10.1136/bmjopen-2020-040801
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the prognostic value of pretreatment serum ferritin in hepatobiliary and pancreas (HBP) cancers

Abstract: Background and objectivesStudies have shown that serum ferritin (SF) has unfavourable prognostic value in hepatobiliary and pancreas (HBP) cancers. This meta-analysis aimed to comprehensively assess the prognostic role of pretreatment SF in patients with HBP cancers.MethodsEligible studies published before January 2020 were obtained through a comprehensive search in the PubMed, Web of Science, Cochrane Library and EMBASE databases. Pooled HRs and 95% CIs were then employed as effect sizes.ResultsSeven studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
(44 reference statements)
1
1
0
Order By: Relevance
“…However, despite these limitations, our study is the first population-based case–control study that presented SF levels of PDAC patients and healthy controls in Taiwan, including a pooled-analysis of six studies to further strengthens the evidence present on the association between SF and pancreatic cancer. The present results are consistent with a recent meta-analysis study from Lin et al, which showed an elevated pretreatment SF is associated with poorer survival outcomes in hepatobiliary and pancreas (HBP) cancer patients, emphasizing the possibility of utilizing SF as the prognostic value for pancreatic cancer 57 . We also aimed to update a previous finding of related topic with the inclusion of new cohort study, since former six studies that have compared SF levels in pancreatic cancer patients and controls were published in either late 1980s or early 1990s.…”
Section: Discussionsupporting
confidence: 93%
“…However, despite these limitations, our study is the first population-based case–control study that presented SF levels of PDAC patients and healthy controls in Taiwan, including a pooled-analysis of six studies to further strengthens the evidence present on the association between SF and pancreatic cancer. The present results are consistent with a recent meta-analysis study from Lin et al, which showed an elevated pretreatment SF is associated with poorer survival outcomes in hepatobiliary and pancreas (HBP) cancer patients, emphasizing the possibility of utilizing SF as the prognostic value for pancreatic cancer 57 . We also aimed to update a previous finding of related topic with the inclusion of new cohort study, since former six studies that have compared SF levels in pancreatic cancer patients and controls were published in either late 1980s or early 1990s.…”
Section: Discussionsupporting
confidence: 93%
“…Up to now, the prognostic value of pretreatment SFC in several types of cancers has been verified. Lin et al [ 41 ] included seven relevant studies involving 1244 patients and demonstrated that elevated pretreatment SFC was related to worse OS (HR = 1.60, P < 0.001) and RFS/progression-free survival (PFS)/time to recurrence (HR = 1.70, P = 0.008) in hepatobiliary and pancreas cancers. Besides, Demir et al [ 12 ] manifested that high SFC was associated with worse survival.…”
Section: Discussionmentioning
confidence: 99%